2015
DOI: 10.1007/s13312-015-0734-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nutritional anemia in adolescents

Abstract: Folate and vitamin B12 deficiencies are more common than iron deficiency in anemic adolescents. Low dietary intake of these nutrients seems to be a significant determinant of their deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 8 publications
7
45
1
5
Order By: Relevance
“…Thomas et al in their study reported B12 deficiency in 50% of subjects whereas Patra et al depicted the same in 42.5% cases . 9,10 Government of India is providing iron and folic acid supplementation along with deworming with albendazole twice yearly. Successful implementation of the program in this region could be justified by low prevalence of severe form of anemia, low worm infestation rate and high frequency of vitamin B12 deficiency without significant decrease in hemoglobin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al in their study reported B12 deficiency in 50% of subjects whereas Patra et al depicted the same in 42.5% cases . 9,10 Government of India is providing iron and folic acid supplementation along with deworming with albendazole twice yearly. Successful implementation of the program in this region could be justified by low prevalence of severe form of anemia, low worm infestation rate and high frequency of vitamin B12 deficiency without significant decrease in hemoglobin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Deena Thomas et al found that 55% had normocytic anemia, 27.5% had microcytic, 8.5% had macrocytic, and 9% had dimorphic anemia. 3 Khanduri et al, found peak incidences of megaloblastic anemia in the age group of 10-30-yearold (48%) with female preponderance (71%) in India.…”
Section: Typing Of Anaemiamentioning
confidence: 99%
“…2 Anemia has a negative effect on cognitive performance in adolescents. 3 Compared to the vast amount of work done in pregnant mothers and young children, there are relatively few published studies in India evaluating deficiencies of Iron, Vitamin B12 and Folate in adolescents having nutritional anemia and its association with severity of anemia. 3 In response to the problem, the national Ministry of Health and Family Welfare (MHFW) launched a nationwide Weekly Iron and Folic Acid Supplementation (WIFS) programme in January 2013-14 UNICEF India has been the partner of choice in supporting the universal roll-out of the programme in 14 major states in India.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In spite of the number of interventions undertaken to combat anemia, its prevalence continues to be high in the adolescent population. In the light of the rapid sociodemographic transition in the country, many of the adolescents are living in urban areas.…”
Section: Introductionmentioning
confidence: 99%